CANNABINOIDS IN THE TREATMENT OF EPILEPSY: A REVIEW OF CURRENT EVIDENCE OF EFFICACY AND SAFETY - Lukić, Stevo; Marković, Pavle; Marković, Katarina (Acta medicae Medianae, 2025)
Despite the use of appropriate pharmacotherapy, a significant proportion of epilepsy patients still struggle with inadequate seizure control. Consequently, there has been a surge in research exploring alternative therapeutic options. Over the past two decades, there has been a growing focus on investigating the potential of cannabinoids as a treatment for epilepsy. While various cannabis-based preparations are available, their compositions and quality vary widely, posing diverse risks. Among these cannabinoids, cannabidiol (CBD) stands out as the only one with scientifically supported benefits, balancing both efficacy and safety after a comprehensive assessment of risks. Notably, CBD distinguishes itself by consistently demonstrating efficacy without inducing psychoactive effects. The highly purified form of CBD has obtained approval from both US and EU regulatory agencies for addressing pharmacoresistant seizures linked to rare and severe childhood-onset epileptic syndromes. Short-term side effects associated with CBD are generally mild to moderate and tend to ameliorate with dose adjustments. However, to gain a deeper understanding of the therapeutic mechanisms, expand the assessment of CBD’s effectiveness across various epilepsy types, compare its efficacy with other antiseizure medications, and ensure long-term safety, additional research studies are imperative.